Perlakuan Panas Kering dan Bakterisida untuk Menekan Infeksi Pantoea stewartii subsp. stewartii pada Benih Jagung Manis - Suswi Nalis; Gede Suastika; Giyanto Giyanto (Jurnal Fitopatologi Indonesia, 2015)
Stewart’s Wilt is an important bacterial disease of sweet corn caused by Pantoea stewartii subsp. stewartii (synonim Erwinia stewartii). This bacteria is a seed transmitted pathogen therefore seed treatment is one method to control stewart’s wilt. The aim of this research was to study the effectiveness of dry heat, bactericide treatment, and their combinations to eliminate P. stewartii subsp. stewartii infection on sweet corn seed without damaging seed quality. The research was conducted in 3 experiments. Experiment I was conducted to determine the treatment window of dry heat and bactericide treatment. The treatment was carried out on sweet corn seed using the P. stewartii subsp. stewartii in vitro. Experiment II was conducted to study dry heat and bactericide treatment on sweet corn seed infested by P. stewartii subsp. stewartii. Experiment III was conducted to study combination of dry heat and bactericide treatment on sweet corn seed infested by P. stewartii subsp. stewartii. The results showed that dry heat treatment at 50 °C for 24 hours was able to eliminate pathogen populations in vitro but was unable to eliminate the 128 pathogen on infected seed (in vivo). Germination tests indicated that seed treatments with dry heat up to 55 °C did not decrease the germination level. The use of bactericide treatment in 100 ppm could reduce the population of bacteria on sweet corn seeds. Bactericide concentration of 150 and 200 ppm could decrease the population of bacteria on sweet corn seeds, however it could cause phytotoxic effect. The combination of bactericide (100 ppm, w/v) ) with dry heat treatment (55 °C for 24 hours) was able to eliminate bacteria on infected seed with seed germination above 85%.